2010
DOI: 10.4314/ajdas.v8i2.52933
|View full text |Cite
|
Sign up to set email alerts
|

Pentazocine abuse in sickle cell anaemia patients: a report of two case vignetes

Abstract: The article aims to draw attention of clinicians to the addictive potentials of Pentazocine use in sickle cell anaemia patients and to highlight some of the associated problems of pentazocine abuse. It also hopes to stimulate the need to review guidelines for the use of analgesics in the management of bone pain crisis or other chronic pains. Two case reports of pentazocine abuse seen in a psychiatry clinic at the University of Ilorin Teaching Hospital (UITH) Ilorin, Nigeria were made. It was found that both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 9 publications
(5 reference statements)
1
24
0
Order By: Relevance
“…Lang and Pilon (1980) reported that PTZ produces minimal euphoria but has some dysphoric effect in the insignificant number of individuals. It was initially thought to be non-addictive ethical medication, but its potential for abuse and dependence was soon observed (Weber and Fromme, 1970;Huskisson, 1974;Makanjuola and Olatunji, 2009). Since then, various 'pharmaco-medicolegal' efforts have been made to significantly minimize its abuse and dependence (Makanjuola and Olatunji, 2009).…”
Section: Adverse Interactions Have Been Observedmentioning
confidence: 99%
See 1 more Smart Citation
“…Lang and Pilon (1980) reported that PTZ produces minimal euphoria but has some dysphoric effect in the insignificant number of individuals. It was initially thought to be non-addictive ethical medication, but its potential for abuse and dependence was soon observed (Weber and Fromme, 1970;Huskisson, 1974;Makanjuola and Olatunji, 2009). Since then, various 'pharmaco-medicolegal' efforts have been made to significantly minimize its abuse and dependence (Makanjuola and Olatunji, 2009).…”
Section: Adverse Interactions Have Been Observedmentioning
confidence: 99%
“…It was initially thought to be non-addictive ethical medication, but its potential for abuse and dependence was soon observed (Weber and Fromme, 1970;Huskisson, 1974;Makanjuola and Olatunji, 2009). Since then, various 'pharmaco-medicolegal' efforts have been made to significantly minimize its abuse and dependence (Makanjuola and Olatunji, 2009). Incidences of drug abuse in Nigeria has persisted from the 1960s till date (Asuni, 1964;Lambo, 1965;Adelekan et al, 2000;Adamson et al, 2010;Onyecho et al, 2016).…”
Section: Adverse Interactions Have Been Observedmentioning
confidence: 99%
“…The use of opioids as a sole agent in the treatment of chronic pain has been identified as a cause of addiction [18]. Pentazocine addiction may present as intense craving for the drug, excessive sweating, body (not bone) pains, signs of needle pricks on the body and poor academic performance [19,20]. Some personality disorders resulting from opioid dependence reflective of dysfunction in the limbic system and higher centres are loss of productivity at work, truancy and criminal tendency ostensibly to raise funds for crave satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Some personality disorders resulting from opioid dependence reflective of dysfunction in the limbic system and higher centres are loss of productivity at work, truancy and criminal tendency ostensibly to raise funds for crave satisfaction. Ultimately, job loss, premature school attrition and other socio-economic are untoward effects of pentazocine abuse [20,21]. It has also been associated with stealing [20,21] and other corrupt practices (to raise money for its purchase) as well as loss of job following associated physical deformity [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation